Atomistic Study on the Mechanical Properties of HOP–Graphene Under Variable Strain, Temperature, and Defect Conditions - Qing Peng; Jiale Li; Xintian Cai; Gen Chen; Zeyu Huang; Lihang Zheng; Hongyang Li; Xiao-Jia Chen; Zhongwei Hu (Nanomaterials)
HOP–graphene is a graphene structural derivative consisting of 5-, 6-, and 8-membered carbon rings with distinctive electrical properties. This paper presents a systematic investigation of the effects of varying sizes, strain rates, temperatures, and defects on the mechanical properties of HOP–graphene, utilizing molecular dynamics simulations. The results revealed that Young’s modulus of HOP–graphene in the armchair direction is 21.5% higher than that in the zigzag direction, indicating that it exhibits greater rigidity in the former direction. The reliability of the tensile simulations was contingent upon the size and strain rate. An increase in temperature from 100 K to 900 K resulted in a decrease in Young’s modulus by 7.8% and 2.9% for stretching along the armchair and zigzag directions, respectively. An increase in the concentration of introduced void defects from 0% to 3% resulted in a decrease in Young’s modulus by 24.7% and 23.1% for stretching along the armchair and zigzag directions, respectively. An increase in the length of rectangular crack defects from 0 nm to 4 nm resulted in a decrease in Young’s modulus for stretching along the armchair and zigzag directions by 6.7% and 5.7%, respectively. Similarly, an increase in the diameter of the circular hole defect from 0 nm to 4 nm resulted in a decrease in Young’s modulus along both the armchair and zigzag directions, with a corresponding reduction of 11.0% and 10.4%, respectively. At the late stage of tensile fracture along the zigzag direction, HOP–graphene undergoes a transformation to an amorphous state under tensile stress. Our results might contribute to a more comprehensive understanding of the mechanical properties of HOP–graphene under different test conditions, helping to land it in potential practical applications.